Limitation of estimation method of current density between battery electrodes by inverse analysis of noisy magnetic field - Yoshinao KISHIMOTO (The Japan Society of Mechanical Engineers, 2017)
A high capacitance battery such as a lithium-ion battery is fabricated by interlaminating electrodes and separators. Since the strength of the separator is relatively low, many situations exist where damage in the separator sheet induces an initiation of short circuit or air gap between the electrodes. In order to prevent serious incidents by such short circuits and air gaps, it is important to evaluate the electrical contact state of the electrodes through the estimation of the current density between the electrodes. This study has developed a novel estimation method of the current density between the electrodes by the inverse analysis of the magnetic field around the battery, and established the methodology to find the limitation of the proposed method against the noisy magnetic field. In order to numerically investigate the basic behavior and the estimation error of the proposed method, a numerical simulation has been performed by using a single cell model consists of two electrodes and one separator. The correct distribution of the current density between the electrodes was given in advance, and the direct analysis was applied to obtain the simulation data of the magnetic flux density. Then the inverse analysis was applied to the simulation data with artificial disturbances. From the results of the numerical simulation, the followings were summarized: 1) It is confirmed that the possibility of the successful estimation depended on the standard deviation of the artificial disturbance. 2) The reference solution in the inverse analysis affected the selection of the regularization parameter and the estimation error against the standard deviation of the artificial disturbance. 3) The proposed method achieved the successful estimation with 90% probability if the disturbance in the magnetic flux density is less than the 30% as far as this numerical simulation.